Innovation : Essentials from Leader to Leader. (J-B Single Issue Leader to Leader., 2013)
Innovation is necessary for creating a bright, competitive future. In this collection, you'll find important insights on innovation drawn from the pages of the award-winning publication Leader to Leader. Written by some of the country's top thought leaders, including Clayton M. Christensen, Margaret J. Wheatley, and Gary Hamel, this collection makes innovation come alive in new and surprising ways. Focusing on different aspects and approaches of innovation, it delivers practical knowledge and advice that can mean the difference in your innovation efforts. Each article is packed with.